Information and the professional scientist and engineer - Baldwin, Virginia A. (Haworth Information Press, 2001)
Current awareness reports at Albany International Research Co. 165 / Alex Caracuzzo -- Supporting the information needs of geographic information systems users in an academic library / Julie Sweetkind-Singer, Meredith Williams -- Interdisciplinary research : a literature-based examination of disciplinary intersections using a common tool, Geographic Information System (GIS) / Robert S. Allen -- New reference works in science and technology / Nancy A. Schiller, editor.